2012
DOI: 10.1007/s00277-012-1463-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age, Charlson comorbidity index, and performance status on treatment of elderly patients with diffuse large B cell lymphoma

Abstract: Treatment intensity will affect outcome in elderly patients with diffuse large B cell lymphoma (DLBCL). We retrospectively reviewed 333 DLBCL patients aged over 60 years who were diagnosed between January 2003 and December 2010 to evaluate the difference between different treatment regimens. The median age was 73 years; 56.8 % of patients received treatment with rituximab-containing regimens. In univariate analysis, patients with younger age, better performance status, early Ann Arbor stage, lower Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
4
41
0
3
Order By: Relevance
“…However, comorbidity was not associated with receiving less than 6 cycles. Surprisingly, although low comorbidity scores predicted better OS and PFS rates, they did not influence the choice of chemotherapy regimen or the ability of patients to complete the whole treatment series [19]. A single-center retrospective study confirmed the negative impact of comorbidities on survival with 3-year OS of 85 and 55% (p = 0.0026) in patients with low CCI (0 or 1) and high CCI (2 or more) scores, respectively [20].…”
Section: Comorbidity and Survivalmentioning
confidence: 90%
See 4 more Smart Citations
“…However, comorbidity was not associated with receiving less than 6 cycles. Surprisingly, although low comorbidity scores predicted better OS and PFS rates, they did not influence the choice of chemotherapy regimen or the ability of patients to complete the whole treatment series [19]. A single-center retrospective study confirmed the negative impact of comorbidities on survival with 3-year OS of 85 and 55% (p = 0.0026) in patients with low CCI (0 or 1) and high CCI (2 or more) scores, respectively [20].…”
Section: Comorbidity and Survivalmentioning
confidence: 90%
“…The number of comorbidities with a score of 3 or 4 and the sum of the score of each organ system represented comorbidity markers. CIRS-G was used in six studies [19][20][21][22]24,36]. However, the coding system was variable according to the authors.…”
Section: Comorbidity Assessment Methodsmentioning
confidence: 99%
See 3 more Smart Citations